Disulfiram Suppressed Peritendinous Fibrosis Through Inhibiting Macrophage Accumulation and Its Pro-inflammatory Properties in Tendon Bone Healing - Qi Zhou; Qi Zhou; Wei Wang; Fujun Yang; Fujun Yang; Hao Wang; Xiaodong Zhao; Yiqin Zhou; Peiliang Fu; Yaozeng Xu (Frontiers in Bioengineering and Biotechnology, 2022)
The communication between macrophages and tendon cells plays a critical role in regulating the tendon-healing process. However, the potential mechanisms through which macrophages can control peritendinous fibrosis are unknown. Our data showed a strong pro-inflammatory phenotype of macrophages after a mouse tendon–bone injury. Moreover, by using a small-molecule compound library, we identified an aldehyde dehydrogenase inhibitor, disulfiram (DSF), which can significantly promote the transition of macrophage from M1 to M2 phenotype and decrease macrophage pro-inflammatory phenotype. Mechanistically, DSF targets gasdermin D (GSDMD) to attenuate macrophage cell pyroptosis, interleukin-1β, and high mobility group box 1 protein release. These pro-inflammatory cytokines and damage-associated molecular patterns are essential for regulating tenocyte and fibroblast proliferation, migration, and fibrotic activity. Deficiency or inhibition of GSDMD significantly suppressed peritendinous fibrosis formation around the injured tendon and was accompanied by increased regenerated bone and fibrocartilage compared with the wild-type littermates. Collectively, these findings reveal a novel pathway of GSDMD-dependent macrophage cell pyroptosis in remodeling fibrogenesis in tendon–bone injury. Thus, GSDMD may represent a potential therapeutic target in tendon–bone healing.